A Polyketide cyclase/dehydrase and lipid transport superfamily gene of Arabidopsis and its orthologue of chickpea exhibit rapid response to wounding - Satheesh, V.; Chidambaranathan, P.; Jagannadham, P.T.; Kohli, D.; Jain, P.K.; Bhat, S.R.; Srinivasan, R. (The Indian Journal of Genetics and Plant Breeding, 2016)
In order to understand the mechanism of stress tolerance it is imperative that we identify factors that govern upstream reactions of stress signalling pathways for multiple stress tolerance. In this study, we have identified a gene, AT5G54170, from Arabidopsis and its orthologue in chickpea, which show rapid response to mechanical wounding. AT5G54170 and its orthologue in chickpea (LOC 101512743) most likely plays a role in the jasmonic acid signalling pathway and the gene is also upregulated in several other stresses making it an ideal candidate for a primary stress-responsive transcript that is involved in the core stress response. Further characterisation of this gene and its promoter, along with its chickpea homologue, could provide valuable information on jasmonic acid signalling pathway and also explore their utility towards engineering stress tolerance in plants.